2010
DOI: 10.4038/cocos.v9i0.2128
|View full text |Cite
|
Sign up to set email alerts
|

River Sand as an Alternative to Top Soil for Raising Coconut Seedlings in Polybags

Abstract: Different combinations of river sand, cow dung and coir dust were compared with the conventional polybag mixtures to study whether seed germination would be affected by the substitution of top soil with river sand. The seed nut germination at 20 weeks was significantly reduced in the sand substituted media, but the difference disappered by 24 weeks from laying. The lower rate of germination was also associated with a reduction of seedling vigour at 30 weeks, probably due to poor seedling nutrition. River sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Related nursery studies [10] concluded that cocoa pod husk-based compost was suitable in combination with topsoil at ratios of 1:2 and 1:3. Earlier work [15] indicated that river sand did not adversely affect germination when substituted for topsoil. However, the rate of germination was slightly delayed and early seedling viguor was reduced in the sand substituted mixtures.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Related nursery studies [10] concluded that cocoa pod husk-based compost was suitable in combination with topsoil at ratios of 1:2 and 1:3. Earlier work [15] indicated that river sand did not adversely affect germination when substituted for topsoil. However, the rate of germination was slightly delayed and early seedling viguor was reduced in the sand substituted mixtures.…”
Section: Introductionmentioning
confidence: 96%
“…The major problem associated with the use of topsoil as seedling medium is scarcity [2]. This scarcity has led to use of various alternatives and mixtures of other media with topsoil for nursing seedlings of other crops such as coconut [7,15]. In raising coconut seedlings, topsoil mixed with river sand in the ratio of 3:1 is a satisfactory mixture for filling the polybags [7].…”
Section: Introductionmentioning
confidence: 99%
“…The system of raising coconut seedlings in polythene bags is now popular in Sri Lanka (Wuidart, 1981;Peries and Everard, 1991) due to its proven benefits to the grower. The limitation of land availability in the tradfc/ tional coconut growing areas has resulted in the cultivation being extended to the non-traditional areas, especially in the Mahaweli region where irriga tion facilities are now available.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is very important to establish seedling nurseries in places close to planting sites. The general potting mixture for raising coconut seedlings in polybags is a 1:2:3 mixture of top soil, cow dung and coir dust (Peries and Everard, 1991). Availability of coir dust is a major constraint in the non-traditional coconut growing areas, specially in dry zone, where other materials such as saw dust, paddy husk, straw and weed trash are in abundance.…”
Section: Introductionmentioning
confidence: 99%